On the dynamics of cutting arc plasmas: the role of the power supply ripple - Prevosto, L. (Advanced Electromagnetics, 2012)
The power sources used in cutting arc torches are usually poorly stabilized and have a large ripple factor. The strong oscillatory components in the voltage and arc current produce in turn, large fluctuations in the plasma quantities. Experimental observations on the dynamics of the non-equilibrium plasma inside the nozzle of a 30 A oxygen cutting torch with a 7 % ripple level of its power source are reported in this work.